"Nobody's paying me to cry": the causes of activist burnout in United States animal rights activists. (4th May 2019) - Gorski, Paul; Lopresti-Goodman, Stacy; Rising, Dallas
ABSTRACT: We examine the causes of activist burnout – a condition in which the accumulative stress associated with activism becomes so debilitating that once-committed activists are forced to scale back on or disengage from their activism – in 17 United States animal rights activists. Following a phenomenological qualitative approach, analysis of interview data revealed three primary categories of burnout causes: 1) intrinsic motivational and psychological factors, 2) organizational and movement culture, and 3) within-movement in-fighting and marginalization. Implications for understandings of activist burnout and the AR movement are discussed.